Repository of Memories - Mumbai Archive Project Team (Jio Institute, 2024)
Saraswati Nakhva remained unmarried and has spent her entire life at the family residence, which is a repository of her life’s memories. ‘I was born here, and I will die here. That is my wish,’ she says.